Experimental and parametric investigation on elastoplastic seismic response of CFST battened built-up columns. Issue 145 (June 2021) - Yuan, Hui-hui; She, Zhi-min; Wu, Qing-xiong; Huang, Yu-fan
Abstract: Previous studies have proven that CFST (concrete-filled steel tube) battened built-up columns (CFST-BBCs) exhibit good hysteresis energy dissipation capacity and deformation capacity under lateral cyclic repeated loading. To further understand the elastoplastic seismic response characteristics of such composite structures under strong earthquakes, two pseudo-dynamic tests of 1/8-scaled CFST-BBC pier specimens were first performed. The acceleration records obtained in the 1995 Kobe Earthquake and the 2008 Wenchuan Earthquake were used to investigate how ground motion intensity, ground motion characteristics, and aftershocks affect the seismic response of the CFST-BBC pier. Meanwhile, an extensive time-history analysis of 17 fiber-based finite element models (FFEMs) under 20 different ground motions was performed to reveal the influence of the ground motion intensity, the same-intensity aftershock, and the main structural parameters on the elastoplastic seismic response of the CFST-BBC pier. Finally, a two-stage checking method suitable for the seismic performance of the CFST-BBC pier under the E1-level frequent earthquake and the E2-level rare earthquake was proposed. Verified by experimental and FFEM analysis results, the proposed checking method can accurately and effectively evaluate the strength and deformation capacity of the CFST-BBC piers under strong earthquakes. Highlights: Elastoplastic seismic response of the CFST-BBC pier under strong earthquakes was investigated by the pseudo-dynamic tests. Aftershocks can markedly aggravate the cumulative damage of the CFST-BBC pier. An extensive time-history analysis was performed to reveal the seismic response characteristics of the CFST-BBC pier. A two-stage checking method for evaluating the strength and deformation capacity of the CFST-BBC pier was proposed.